(untitled) (Mūzikas akadēmijas raksti, 2024)
Issues of identity appear in Russian traditional music and in revival discourses in most different ways. In rural settings regional and local identities are rooted much deeper than ideas of ‘Russianness’ in music. These small-scale identities can be closely related to ethnomusical boundaries, especially to distinct geographical ranges of instrumental tunes. Their toponymic and ethnonymic terminologies are of relatively late origin. Traditionally local repertoires are conceptualised much more by functional and structural criteria. The newer terminology can be explained with a heightened mobility of the population as well as with a growing prestige of locality in the last decades.